2021
DOI: 10.1002/adem.202100877
|View full text |Cite
|
Sign up to set email alerts
|

Material Selection Methodology for an Induction Welding Magnetic Susceptor Based on Hysteresis Losses

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adem.202100877.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…From this point of view, the studies carried out since 2010 by Ceylan et al, who reported using Fe2O3/Fe3O4@SiO2; MagSilica, impregnated with nanoparticles of Pd 16 or Au 40 , should be noted. Specifically, the research focused on the ability of radiofrequencypowered superparamagnetic MagSilica nanoparticles to act as heating agents for a wide range of stoichiometric reactions in flow chemistry [10][11][12].…”
Section: Applications Of Induction Heating To Non-polymeric Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…From this point of view, the studies carried out since 2010 by Ceylan et al, who reported using Fe2O3/Fe3O4@SiO2; MagSilica, impregnated with nanoparticles of Pd 16 or Au 40 , should be noted. Specifically, the research focused on the ability of radiofrequencypowered superparamagnetic MagSilica nanoparticles to act as heating agents for a wide range of stoichiometric reactions in flow chemistry [10][11][12].…”
Section: Applications Of Induction Heating To Non-polymeric Materialsmentioning
confidence: 98%
“…Very recently, Martin and co-workers [40] investigated the effectiveness of different susceptors made of Fe, Ni, and Fe 3 O 4 particles in polypropylene (PP) and PEEK matrices. On the basis of the magnetic field amplitude produced by the welding setup, the thermal properties of the polymers and particles used for the susceptor and the magnetic hysteresis of the magnetic particles allowed for predicting the optimum heating rates.…”
Section: Induction Welding Of Thermoplastic Systemsmentioning
confidence: 99%